Ascites dropsy gestosica - Uranga Imaz, A. (2015)
The authors present two outstanding observations of widespread ascites in other toxemic many patients, the first was a secundigesta with a history of hypertensive gestosis in their previous pregnancy. In the current severe hypertensive pregnancy toxemia (high blood pressure, large edema, proteinuria). With 6 and a half months pregnant discontinuation caesarean operation is performed. Ascites of more than 6 liters and free peritoneal cavity. The patient recovers quickly and definitely in their abdominal involvement, with great functional improvement. The second point concerns a primigravida patient with family and personal history of hypertension. 5 months pregnant and a half; severe hypertension, generalized edema, proteinuria, high uric acid, hipoprotidemia marked. Despite the harsh treatment, the picture did not improve and the pregnancy is interrupted by cesarean section after 6 months and three weeks. Ascites 3 liters. The child of 1,200 grams. dies at 48 hours. The absence of strange process takes place in the womb. The patient improved rapidly. It is pregnant again eight months of the termination of first and is hospitalized. And complies with short trips during her second pregnancy that runs smoothly and normotensive, but with a decreased plasma clearance of urea. It has its birth at 8 months and a half with a healthy child of 2,950 grams. They refer to the difficulty prognosis in these patients and offer bibliographic history of this rare complication of hypertensive toxemia.